Influence of pr-M cleavage on the heterogeneity of extracellular dengue virus particles - Junjhon J. (2014)
During dengue virus replication, an incomplete cleavage of the envelope glycoprotein prM, generates a mixture of mature (prM-less) and prM-containing, immature extracellular particles. In this study, sequential immunoprecipitation and cryoelectron microscopy revealed a third type of extracellular particles, the partially mature particles, as the major prM-containing particles in a dengue serotype 2 virus. Changes in the proportion of viral particles in the pr-M junction mutants exhibiting altered levels of prM cleavage suggest that the partially mature particles may represent an intermediate subpopulation in the virus maturation pathway. These findings are consistent with a model suggesting the progressive mode of prM cleavage. Copyright © 2010, American Society for Microbiology. All Rights Reserved.